Going under Dr. Robot's knife: the effects of robot anthropomorphism and mortality salience on attitudes toward autonomous robot surgeons - Sönmez, Fatih (Taylor & Francis Ltd, 2022)
Objective This study sought to experimentally test two potential factors that could affect the consumer acceptance of autonomous robot surgeons: anthropomorphism and mortality salience. The study also investigated the effect of gender and its interaction with anthropomorphism on attitudes toward autonomous robot surgeons. Design and Main Outcome Measures A between-subjects experiment with a 2 (anthropomorphism: low vs. high) x 2 (mortality salience: no vs. yes) factorial design was conducted (N = 196). The trust in the autonomous surgical robot and the willingness to undergo autonomous robotic surgery served as the dependent variables. Results When death thoughts were not active, the human-likeness of the autonomous surgical robot significantly increased the trust in the robot and the willingness to undergo autonomous robotic surgery. Activating death thoughts did not further increase the positive attitudes toward the higher-anthropomorphic robot, while it significantly increased the trust in and the willingness to be operated on by the lower-anthropomorphic robot, rendering both robots comparable. This study also found that women had less positive attitudes toward the autonomous robot surgeon, regardless of the robot's human-likeness. Conclusion Anthropomorphism and mortality salience can both positively affect the acceptance of autonomous robotic surgery but only in the absence of one another.
Keywords: Anthropomorphism; mortality salience; autonomous robot surgeon; robotic surgery; consumer attitudes; Preoperative Anxiety; Gender-Differences; Enhances Connectedness; Increases Trust